POST-CATASTROPHIC CITY TEXT: THE CITY READING IN THE CITY IN THE POSTWAR EAST AND CENTRAL EUROPE (City: History, Culture, Society, 2020)
In the material, the author addresses a multidimensional memory problem - not only as a constituent of social life but also as a feature of its functioning in urban space. The author presents the interpretations of memory against the background of urban transformations. The complexity and multidimensionality of this phenomenon are emphasized not only in the usual methodological field but also in literary practice. Literature acts as a means of accumulating memory despite the disappearance or destruction of one or the other in urban space. The traumatic experience is of particular importance. The example of the twentieth century reflects the various cases of the existence of memories of the tragic past. Kyiv, Lviv, Wroclaw, Kaliningrad and several other cities during the Second World War have faced the transformation of the usual landscape. That was both the realities of time and the policies against certain groups who have been harassed and destroyed. The practice of work and interaction with one or another component of the past, measures of governmental bodies are analyzed. After these tragic periods, the memory in a peculiar manner was lost. The cities in the region in one way or another came to return and actualization of this experience in the modern world. Critical in this process is the literary practice that "returns" and "opens" the memory of urban space. Complex topics require the involvement of a large number of disciplines in order to form an objective vision of the urban past.
Keywords: urbanization; memory; Eastern and Central Europe; urban landscape